ChemInform Abstract: Enantioselective Hydroacylation of N‐Vinylindole‐2‐carboxaldehydes. Issue 25 (24th June 2014) - Ghosh, Avipsa; Stanley, Levi M.
Abstract A rhodium‐catalyzed intramolecular hydroacylation of aldehydes (I) leads to chiral tricyclic indoles (II) with high enantioselectivity.